Combined Therapy of Locally Advanced Oesophageal and Gastro-Oesophageal Junction Adenocarcinomas: State of the Art and Aspects of Predictive Factors - Vošmik, Milan; Kopecký, Jindřich; John, Stanislav; Kubeček, Ondřej; Lochman, Petr; Banni, Aml Mustafa; Hruška, Libor; Sirák, Igor (Cancers, 2021)
The following main treatment approaches are currently used in locally advanced adenocarcinomas of the oesophagus and gastrooesophageal junction (GOJ): preoperative chemoradiotherapy and surgery, and perioperative chemotherapy and surgery. While preoperative chemoradiotherapy is used primarily in oesophageal tumours, perioperative chemotherapy is the treatment of choice in Western countries for gastric cancer. The optimal treatment strategy for GOJ adenocarcinoma is still not clear. In comparison to other malignancies, biomarkers are used as predictive factors in distal oesophageal and GOJ adenocarcinomas in a very limited way, and moreover, only in metastatic stages (e.g., HER2 status, or microsatellite instability status). The aim of the article is to provide an overview of current treatment options in locally advanced adenocarcinomas of oesophagus and GOJ based on the latest evidence, including the possible potential of predictive biomarkers in optimizing treatment.
Keywords: gastro-oesophageal junction; adenocarcinoma; oesophagus; perioperative chemotherapy; preoperative chemoradiotherapy